Selective lesion of cholinergic neurons in the medial septum by 192 IgG-saporin impairs learning in a delayed matching to position T-maze paradigm - Johnson, David A; Zambon, Natalie J; Gibbs, Robert B (Brain research, 2002)
This study examined whether selective destruction of cholinergic neurons in the medial septum impairs acquisition of a delayed matching-to-position (DMP) spatial memory task. Either the selective immunotoxin 192 IgG-saporin (SAP; 0.22 or 1.0 μg) or the non-selective excitatory neurotoxin ibotenate (IBO; 5 μg), was infused directly into the medial septum of rats. Both doses of SAP, but not IBO, significantly impaired acquisition of the DMP task and blunted the initial alternating behavior of the rats in the T-maze. Histochemical staining revealed that both doses of SAP produced a near complete depletion of choline acetyltransferase (ChAT)-positive neurons in the medial septum. Some loss of parvalbumin staining was observed following administration of the higher dose, but not the lower dose, of SAP. In contrast, IBO produced a nearly complete depletion of parvalbumin-positive staining throughout the medial septum. IBO also produced a loss of ChAT-positive neurons and considerable local damage in the medial septum around the area of injection; however, many ChAT-positive neurons in the medial septum distal to the injection remained. A significant correlation between the number of days to reach criterion and ChAT activity in the frontal cortex and hippocampus was observed. The results suggest that low doses of SAP can be used to selectively destroy cholinergic neurons in the medial septum, and that selective destruction of these neurons significantly impairs acquisition of the DMP task. We propose that acquisition of the DMP task is a sensitive behavioral assay for the selective loss of basal forebrain cholinergic projections.